Supplementation of nitric oxide and spermidine alleviates the nickel stress-induced damage to growth, chlorophyll metabolism, and photosynthesis by upregulating ascorbate–glutathione and glyoxalase cycle functioning in tomato - Qin, Cheng; Shen, Jie; Ahanger, Mohammad Abass (Frontiers in Plant Science, 2022)
Experiments were conducted to evaluate the role of exogenously applied nitric oxide (NO; 50 µM) and spermidine (Spd; 100 µM) in alleviating the damaging effects of Ni (1 mM NiSO46H2O) toxicity on growth, chlorophyll metabolism, photosynthesis and mineral content in tomato. Treatment of Ni reduced plant height and dry mass, content of glutamate 1-semialdehyde, δ-Amino levulinic acid, prototoporphyrin IX, Mg-prototoporphyrin IX, total chlorophyll and carotenoids significantly, however application of NO and Spd alleviated the decline considerably. Supplementation of NO and Spd mitigated the Ni induced decline in photosynthesis, gas exchange and chlorophyll fluorescence parameters. Ni imposed oxidative damage while as application of NO, Spd and NO + Spd reduced the oxidative stress parameters significantly under normal and Ni toxicity. Application of NO and Spd up-regulated the functioning of antioxidant system and the activity of glyoxylase enzymes reflecting in significant reduction in the oxidative effects and methylglyoxal accumulation. Tolerance against Ni was further strengthened by the accumulation of proline and glycine betaine due to NO and Spd application. Decline in uptake of essential mineral elements including N, P, K and Mg was alleviated by NO and Spd. Hence individual as well as combined supplementation of NO and Spd affectively alleviates the damaging effects of Ni on tomato.